Content analysis of economic and technical information on Spain’s urban transport companies’ web pages - Benítez Quevedo, Cecilia; Balboa La Chica, Pedro M.; Mesa Mendoza, Margarita; Suárez Falcón, Heriberto (Cooperativismo & Desarrollo, 2017)
Purpose: This article analyzes to what extent do companies that provide urban passenger transport in Spain publish useful information on their websites that allows evaluating the management carried out in a given period. Themes: The first step was to select the sample of companies from those providing the service in the capitals of Spanish provinces, since this are the most relevant municipalities and taking into account their fundamental activity and their web pages’ layout. Development: A questionnaire of diverse items is then applied to the sample. The questionnaire emphasizes on aspects related to the companies’ organization, activity, technical production means, consumptions, human resources and economic information. Conclusions: Results are presented, both in terms of the population size of provincial capitals and in relation to the direct or indirect management of the service. These results reveal the scarce economic information offered, with the exception of tariffs and the number of lines. In addition, it was found that companies with direct management provide more information than those that manage the service indirectly.